Immunohistological detection of small particles of Echinococcus multilocularis and Echinococcus granulosus in lymph nodes is associated with enlarged lymph nodes in alveolar and cystic echinococcosis. - Johannes Grimm; Juliane Nell; Andreas Hillenbrand; Doris Henne-Bruns; Julian Schmidberger; Wolfgang Kratzer; Beate Gruener; Tilmann Graeter; Michael Reinehr; Achim Weber; Peter Deplazes; Peter Möller; et al. (Public Library of Science (PLoS), 2020)
Background Alveolar (AE) and cystic echinococcosis (CE) in humans are caused by the metacestode of the tapeworms Echinococcus multilocularis and Echinococcus granulosus sensu lato (s.l.). Immunohistochemistry with the monoclonal antibodies (mAb) Em2G11, specific for AE, and the mAb EmG3, specific for AE and CE, is an important pillar of the histological diagnosis of these two infections. Our aim was to further evaluate mAb EmG3 in a diagnostic setting and to analyze in detail the localization, distribution, and impact of small particles of Echinococcus multilocularis (spems) and small particles of Echinococcus granulosus s.l. (spegs) on lymph nodes. Methodology/principal findings We evaluated the mAb EmG3 in a cohort of formalin-fixed, paraffin embedded (FFPE) specimens of AE (n = 360) and CE (n = 178). These samples originated from 156 AE-patients and 77 CE-patients. mAb EmG3 showed a specific staining of the metacestode stadium of E. multilocularis and E. granulosus s.l. and had a higher sensitivity for spems than mAb Em2G11. Furthermore, we detected spegs in the surrounding host tissue and in almost all tested lymph nodes (39/41) of infected patients. 38/47 lymph nodes of AE showed a positive reaction for spems with mAb EmG3, whereas 29/47 tested positive when stained with mAb Em2G11. Spegs were detected in the germinal centers, co-located with CD23-positive follicular dendritic cells, and were present in the sinuses. Likewise, lymph nodes with spems and spegs in AE and CE were significantly enlarged in size in comparison to the control group. Conclusions/significance mAb EmG3 is specific for AE and CE and is a valuable tool in the histological diagnosis of echinococcosis. Based on the observed staining patterns, we hypothesize that the interaction between parasite and host is not restricted to the main lesion since spegs are detected in lymph nodes. Moreover, in AE the number of spems-affected lymph nodes is higher than previously assumed. The enlargement of lymph nodes with spems and spegs points to an immunological interaction with the small immunogenic particles (spems and spegs) of Echinococcus spp.